Articular eminence inclination in medieval and contemporary Croatian population - Josip Kranjčić; Mario Šlaus; Marin Vodanović; Sanja Peršić; Denis Vojvodić (Acta Clinica Croatica, 2016)
Articular eminence inclination (AEI) of the temporomandibular joint leads the mandible in its movements. Therefore, the aim of the present study was to determine AEI values in medieval (MP) and recent (RP) Croatian population. The study was carried out on two groups of specimens: first group with 30 MP human dry skulls, while the other, serving as control group consisted of 137 dry skulls. The AEI was measured on lateral digital skull images as the angle between the best fit line drawn along the posterior wall of the articular eminence and the Frankfurt horizontal plane. No statistically significant (p>0.05) differences between the left and right side AEI were found between MP skulls and RP skulls. The mean value of MP AEI was 45.5˚, with a range of 20.9˚-64˚. The mean RP AEI value was steeper (61.99˚), with a range of 30˚-94˚. Difference between the mean MP and RP AEI values was statistically significant (p<0.05). Values of AEI vary a lot. Nonsignificant differences between the left and right side AEI confirmed the natural left-right side asymmetry. The values of AEI differ between the RP and MP groups, most probably due to different type of food consumption in medieval time, and consequently different masticatory loads and forces.